Philippines : 2021 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Philippines. (IMF Staff Country Reports; Country Report ;, 2021)
The economy is recovering after a major, pandemic-induced economic downturn. The authorities have deployed a comprehensive set of policy responses that have helped to mitigate the socioeconomic impact and maintain financial stability. The economic recovery slowed in the first half of 2021 due to a second wave of COVID-19 infections. Vaccination has started and is poised to accelerate from midyear.